Computer and information sciences : 31st International Symposium, ISCIS 2016, Kraków, Poland, October 27-28, 2016, Proceedings /: 31st International Symposium, ISCIS 2016, Kraków, Poland, October 27-28, 2016, Proceedings. (2016) - Unknown
No abstract available